Pesan Teologis Penggunaan Nama Gabungan Allah אֵ֣ל שַׁדַּ֔י (El-Shaddai) dalam Pentateukh - Ragil Kristiawan (Jurnal Ilmiah Tafsir Alkitab, 2024)
Abstract The Pentateuch gives the fact that for the first time God's composite name is introduced and used in the Bible. One of the famous names of God is El-Shaddai where systematics experts always associate it with the power of God alone. The emergence of El-Shaddai in the Pentateuch provides the most significant theological message than any other part. This research seeks to explore that theological message. Using a topical approach to the Pentateuch text regarding the emergence of El-Shaddaí, several theological messages are produced: First, El-Shaddai is the One who is able to fulfill all His promises even though they seem impossible in the eyes of man (Gen. 17:1). Second, El-Shaddai is a source of blessing that will bless His people with good things (Gen. 28:3).  Third, El-Shaddai is the One who definitely fulfills all His promises. His name is the guarantee of the fulfillment of what has been promised (Gen. 58:3; Ex. 6:2). Fourth, El-Shaddai will arrange all good things for the good of His own people. (43:14). Lastly, El-Shaddai will continue to protect His people from curses and will turn them into blessings (Num. 24:4, 16). God's miraculous providence will apply to the people who are faithful to Him.